Pelatihan Pembuatan Konten Digital menggunakan Canva sebagai Media Informasi bagi Perangkat Kelurahan Tasikmadu, Kota Malang - Abdullah, Moch Zawaruddin; Jarnuzi, Ahmad; Sukmana, Septian Enggar; Pamenang, Muhammad Unggul; Suryadi, Satrio Binusa; Amalia, Astrifidha Rahma (LPPM IT Telkom Purwokerto, 2025)
The digital content creation training for Tasikmadu Village officials in Malang City was organized with the aim of enhancing skills in creating effective digital content as an informative medium. With the rapid development of the digital era, village officials must present information in an engaging and interactive manner to make it more easily accepted by the public. This training was meticulously planned to provide an understanding of the fundamental concepts of graphic design, appropriate visual media selection, and messaging strategies tailored to the audience's requirements. Participants learned how to create attractive and relevant visual content, such as infographics, using the Canva app in both web and mobile versions. Furthermore, the training was practical and interactive, with direct demonstrations and content creation exercises for the participants. The training resulted in a significant improvement in participants' abilities to effectively use visual elements, organize appealing layouts, and present information in a more dynamic and easily understandable manner. This training is expected to help village officials maximize the use of digital content for more effective communication with the community.